2021
DOI: 10.3390/microorganisms9050903
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore Sequencing Is a Credible Alternative to Recover Complete Genomes of Geminiviruses

Abstract: Next-generation sequencing (NGS), through the implementation of metagenomic protocols, has led to the discovery of thousands of new viruses in the last decade. Nevertheless, these protocols are still laborious and costly to implement, and the technique has not yet become routine for everyday virus characterization. Within the context of CRESS DNA virus studies, we implemented two alternative long-read NGS protocols, one that is agnostic to the sequence (without a priori knowledge of the viral genome) and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…Despite the detection of minority DRMs in treatment-experienced patients at read frequencies higher than 30% by MinION sequencing, they were not detected by Sanger-based sequencing. The minority variants described in this study were not located in homopolymer regions generally associated with false base calling on different NGS platforms, including the Oxford Nanopore MinION ( 22 ). In addition, they were supported by a depth of coverage at drug resistance sites of >40, per-base sequencing quality of >20, and read frequency of >30%.…”
Section: Discussionmentioning
confidence: 74%
“…Despite the detection of minority DRMs in treatment-experienced patients at read frequencies higher than 30% by MinION sequencing, they were not detected by Sanger-based sequencing. The minority variants described in this study were not located in homopolymer regions generally associated with false base calling on different NGS platforms, including the Oxford Nanopore MinION ( 22 ). In addition, they were supported by a depth of coverage at drug resistance sites of >40, per-base sequencing quality of >20, and read frequency of >30%.…”
Section: Discussionmentioning
confidence: 74%
“…Due to the small genome size of plant viruses, ranging from 4 to 30 kb [75], long read sequencing can capture entire genome segments in a single read. For plant viruses, long read sequencing has been used on geminiviruses [76], tombusviridae [77], and several potyviruses including Wheat streak mosaic virus [78], Plum pox virus [79] and Yam mild mosaic virus [80]. However, the host plants in these studies were all crop plants, with the exception of the geminiviruses found in Medicago arborea, a shrub in the Fabaceae family [76].…”
Section: Challenges In Hts and Bioinformaticsmentioning
confidence: 99%
“…For plant viruses, long read sequencing has been used on geminiviruses [76], tombusviridae [77], and several potyviruses including Wheat streak mosaic virus [78], Plum pox virus [79] and Yam mild mosaic virus [80]. However, the host plants in these studies were all crop plants, with the exception of the geminiviruses found in Medicago arborea, a shrub in the Fabaceae family [76]. In these studies, a variety of DNA and RNA HTS library preparation protocols are used, and the choice of library preparation affects the virus detection sensitivity.…”
Section: Challenges In Hts and Bioinformaticsmentioning
confidence: 99%
“…Using this advanced approach, by assessing the long overlaps among multiplex amplicons, the accurately assembled and complete viral genome can be obtained, which can facilitate the rapid genomic surveillance of PPRV for better understanding its pathogenicity, evolution and transmission. Although a protocol for Oxford nanopore sequencing of PPRV has been established, adoption of the technology has been limited due to concerns around accuracy and high error rates associated with homopolymer lengths [15]. The nanopore device exhibits lower read-level sequencing accuracy than its short-read platform counterparts [16].…”
Section: Introductionmentioning
confidence: 99%